2016
DOI: 10.3208/jgssp.irq-05
|View full text |Cite
|
Sign up to set email alerts
|

Sand and stone columns in soft soil at different relative densities

Abstract: The technique of sand or stone columns is widely used to improve the load carrying capacity and reduce the settlement of soft soils. The technique consists of excavating holes of specific dimensions and arrangement in the soft soil and backfilling them with either stone or sand particles. The efficiency of the technique depends primarily on the type of the backfill material (sand or stone) and gradation as well as the placement relative density. In the present research, holes 50 mm in diameter and 300 mm in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The column backfill material is commonly selected based on suitability, economy and availability (Baumann and Bauer 1974;Zukri and Nazir 2018). Crushed stone is often preferred due to its high friction angle and stiffness (Al Saudi et al 2016). However, sand could also be used where crushed stone is unavailable (Kadhim et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The column backfill material is commonly selected based on suitability, economy and availability (Baumann and Bauer 1974;Zukri and Nazir 2018). Crushed stone is often preferred due to its high friction angle and stiffness (Al Saudi et al 2016). However, sand could also be used where crushed stone is unavailable (Kadhim et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…IS 15284 (2003) broadly suggests that well-graded granular materials ranging from 2 to 75 mm may be used as column backfill. However, almost no specifications are currently available in the published scientific literature on the optimal particle size range (PSR) of column backfill (Al Saudi et al 2016). Siahaan et al (2018) also mentioned that the role of particle size of the column backfill on the geotechnical behaviour of granular columns remains relatively under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…After… completion of… the final… layer, the… top surface… was scraped… and… leveled to… get as near… as a flat… surface. The models…consist of… eight columns… at area… replacement ratio… of (0.196) in… a square pattern the… configuration of… the columns… shown in figure (4). PVC… tube (50 mm… in diameter and 500…mm in… height) was… inserted vertically… to the required… depth (300 mm… from the… top surface) and… the soil was… removed completely… inside the… tube.…”
Section: Model Preparation and Testingmentioning
confidence: 99%
“…The outcomes of the experiment revealed that the micro piles will resist deflection of the soil and expand the zone at failure if the micropile depth is long enough relative to the thickness of the footing's failure surface. However, a field study examining the application of micro piles for methods of ground improvement has been done [15][16][17].…”
Section: Introductionmentioning
confidence: 99%